A role for peroxisome proliferator‐activated receptor gamma in resveratrol‐induced colon cancer cell apoptosis. Issue 9 (30th June 2014) - Aires, Virginie; Brassart, Bertrand; Carlier, Annie; Scagliarini, Alessandra; Mandard, Stéphane; Limagne, Emeric; Solary, Eric; Martiny, Laurent; Tarpin, Michel; Delmas, Dominique
<x xml:space="preserve">Abstract</x> Scope Resveratrol may function as a chemopreventive agent. A recent clinical study demonstrates a reduction in tumor cell proliferation in colorectal patients receiving repeated oral ingestion of resveratrol. However, gaps remain in our knowledge of the molecular mechanisms by which resveratrol exerts its chemopreventive effect. We have previously demonstrated that resveratrol induces apoptosis in colon cancer cells and that resveratrol can sensitize chemoresistant colon cancer cells to various drugs. Based on its ability to activate peroxisome proliferator‐activated receptor gamma (PPARγ) in colon cancer cells, we sought to determine the implication of this nuclear transcription factor in resveratrol‐induced apoptosis. Methods and results Transient transfection of cancer cells with a dominant‐negative PPARγ mutant or treatment with a PPARγ antagonist (GW9662) reversed the inhibitory effect of resveratrol. Moreover, GW9662 prevented disruption of the cell cycle induced by resveratrol and consequently abrogated resveratrol‐induced apoptosis. Tumor cell death was potentiated by combining resveratrol with rosiglitazone, a PPARγ agonist. Conclusion The results show that PPARγ plays a role in resveratrol‐induced apoptosis of colon carcinoma cells. The combination of resveratrol with a PPARγ agonist could be a promising pharmacological approach for treatment of colorectal cancer.